Selection of prospective parents among Indian and exotic Sesame (Sesamum indicum L.) for marker assisted breeding - Prasad, Ranjana; Gangopadhyay, Gaurab (The Indian Journal of Genetics and Plant Breeding, 2017)
Five exotic sesame accessions were selected by combined phenomic and genomic approaches as prospective male parents to introgress certain desirable traits as lighter testa colour, synchrony in capsule maturation and non-shattering habit of mature capsules for improvement of one selected Indian accession. One SCAR marker, specific to the female parent (Indian) and certain SSR allelic polymorphism between female and five prospective exotic male parents are reported, which will be helpful for marker assisted breeding of sesame.